2018
DOI: 10.7150/jca.26858
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Laparoscopic Total Gastrectomy for Elderly Gastric Cancer Patients

Abstract: Purpose: The purpose of this study was to compare the short- and long-term outcomes after laparoscopic total gastrectomy (LTG) between elderly and non-elderly patients with gastric cancer.Methods: A retrospective analysis was performed using clinical and follow-up data from 168 patients treated with LTG for gastric cancer at our institution from January 2010 to December 2017. For this study, the short- and long-term outcomes (including tumor recurrence rate, disease-free survival rate, and overall survival rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…In the present study, there were no significant differences in the other short-term outcomes; thus, our surgical procedures would be considered acceptable. The only study limited to LTG showed no difference in OS or DSS (19). However, previous studies on the long-term outcomes of laparoscopic gastrectomy have reported that OS in an elderly group was poorer than that in non-elderly groups and that the DSS rates of the two groups were equivalent.…”
Section: Discussionmentioning
confidence: 81%
“…In the present study, there were no significant differences in the other short-term outcomes; thus, our surgical procedures would be considered acceptable. The only study limited to LTG showed no difference in OS or DSS (19). However, previous studies on the long-term outcomes of laparoscopic gastrectomy have reported that OS in an elderly group was poorer than that in non-elderly groups and that the DSS rates of the two groups were equivalent.…”
Section: Discussionmentioning
confidence: 81%
“…Patients undergoing primary surgery are usually older and have several comorbidities, and are therefore not deemed fit enough for chemotherapy. 29 , 30 It is possible that in these patients, additional findings are more frequently detected on FDG-PET/CT or during SL, for which further diagnostics are required. Other confounding factors might also contribute to increasing waiting times.…”
Section: Discussionmentioning
confidence: 99%
“…However, LTG is more difficult due to technology than laparoscopic distal gastrectomy, reconstruction is complicated, and it has been reported that the complication rate is high in the real world[ 67 ]. It has been reported that LTG does not increase complications even in the elderly[ 68 ]; however, LTG has been reported to have anastomotic leakage[ 69 ] and complications[ 70 ]. Only well-trained laparoscopic teams should perform LTG.…”
Section: Optimal Surgical Treatment For Elderly Gcmentioning
confidence: 99%